Engineering Mineralized and Load Bearing Tissues - Bertassoni, Luiz E.; Coelho, Paulo G. (Advances in Experimental Medicine and Biology, 2015)
This book offers a comprehensive overview of current challenges and strategies to regenerate load-bearing and calcified human tissues, including bone, cartilage,tendon, ligaments and dental structures (dentin, enamel, cementum and periodontal ligament). Tissue engineering has long held great promises as an improved treatment option for conditions affecting mineralized and load-bearing structures in the body. Although significant progress has been achieved in recent years, a number of challenges still exist. Scaffold vascularization, new biofabrication methods (3D printing, lithography, microfabrication), peptide conjugation methods, interface engineering, scaffold mechanical properties, iPS cells, organs-on-a-chip, are some of the topics discussed in this book. More specially, in the first section readers will find an overview of emerging biofabrication methods. In section 2, applied strategies for regeneration of (2.1) bone, cartilage and ligament, as well as (2.2) dentin, cementum, enamel and periodontal ligament are discussed across 14 chapters. While other volumes have addressed the regeneration of individual tissues, or exclusively focused on different regenerative strategies, the focus of this work is to bring together researchers integrating backgrounds in materials sciences, engineering, biology, mechanics, fluidics, etc, to address specific challenges common to regeneration of several load-bearing and calcified tissues. Therefore, this book provides a unique platform to stimulate progress in the regeneration of functional tissue substitutes. We envision that this book will represent a valuable reference source for university and college faculties, post-doctoral research fellows, senior graduate students, and researchers from R&D laboratories in their endeavors to fabricate biomimetic load bearing tissues.